Health information sharing – conceptual clarification and exploratory analysis in the context of mammography screening - Paula Stehr; Elena Link; Constanze Rossmann (Information Research: An International Electronic Journal)
Introduction. Information sharing is an important but under researched type of health information behaviour. In this study, we explore the characteristics of sharing behaviours, their reasons and determinants in the context of mammography screening.